118 Vessel health and preservation tool: putting the child first in vascular access. (December 2018) - Banaghan, M; Dunn, H
Abstract : Summary: In July 2017, Great Ormond Street Hospital introduced the first paediatric adaptation of the Vessel Health and Preservation tool (VHP), informing a safe and considerate approach to vascular access. Whilst the overall aim was to reduce the number extravasation injuries and improve vessel health preservation, the tool outlines a template to advocate 'Using the right line, at the right time, by the right person'. Utilising quality improvement and PDSA methodology has allowed the team to leverage pilot site testing to refine the tool and supporting documentation. Objectives: The VHP aims to standardise the approach to vein assessment and support appropriate escalation at GOSH, increasing awareness of the impact of an individual's decisions in vascular access on patient experience and outcomes. Patient/parent involvement: Patients and families have been involved throughout the project; filming their experiences, using case studies to educate and raise awareness, collating feedback through surveys, a parent representative on the project team, and regular communications with our Young Peoples' Forum. Results: Staff report that the tool has 'given me the confidence to escalate', 'helps prevent distress in children with excess attempts of cannulation', and that 'it is an easy to use intuitive tool…that helps guide your management of a patient and tries to minimise the harm in the circumstance where they are known difficult access.' (Staff Survey, GOSH, April 2017). Data shows that the implementation of the tool has not had a negative impact on supporting services; Venous Access Facilitators data shows that since the tool was introduced all referrals have been appropriate No increase in demand for central line insertion Reduction in extravasation injuries referred to the Plastics Team sustained since January 2017 Reduction in number of patients with more than two unsuccessful cannulation attempts before referral to the vascular access team since November 2017.